2022
DOI: 10.1186/s13054-022-04199-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal versus conventional cardiopulmonary resuscitation for refractory out-of-hospital cardiac arrest: a secondary analysis of the Prague OHCA trial

Abstract: Background Survival rates in refractory out-of-hospital cardiac arrest (OHCA) remain low with conventional advanced cardiac life support (ACLS). Extracorporeal life support (ECLS) implantation during ongoing resuscitation, a method called extracorporeal cardiopulmonary resuscitation (ECPR), may increase survival. This study examined whether ECPR is associated with improved outcomes. Methods Prague OHCA trial enrolled adults with a witnessed refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 27 publications
0
45
0
6
Order By: Relevance
“…Indeed, survival with good neurological recovery between shockable and non-shockable initial rhythms was significantly different, i.e., 49% vs. 8% in the invasive strategy and 33% vs. 2% in the standard ALS. Another secondary analysis also reported that ECPR improved 180-day survival in patients who did not achieve pre-hospital ROSC [ 29 ]. In fact, the overall 180-day survival in patients without pre-hospital ROSC increased from 1.2% in those receiving conventional ALS to 23.9% in those treated with ECPR [ 29 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, survival with good neurological recovery between shockable and non-shockable initial rhythms was significantly different, i.e., 49% vs. 8% in the invasive strategy and 33% vs. 2% in the standard ALS. Another secondary analysis also reported that ECPR improved 180-day survival in patients who did not achieve pre-hospital ROSC [ 29 ]. In fact, the overall 180-day survival in patients without pre-hospital ROSC increased from 1.2% in those receiving conventional ALS to 23.9% in those treated with ECPR [ 29 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Another secondary analysis also reported that ECPR improved 180-day survival in patients who did not achieve pre-hospital ROSC [ 29 ]. In fact, the overall 180-day survival in patients without pre-hospital ROSC increased from 1.2% in those receiving conventional ALS to 23.9% in those treated with ECPR [ 29 ]. Rapid deployment of veno-arterial extracorporeal circulation during ongoing CPR is, therefore, a promising approach for patients with refractory non-traumatic OHCA and has demonstrated improved outcomes in selected patients with favorable cardiac arrest circumstances, although limited data exist regarding the best practices for ECPR [ 14 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Some of the patients for whom resuscitation was initiated in a public space may have been transported to hospital under continued resuscitation, since declaring a patient dead “on the street” involves significant administrative work. With extracorporeal cardiopulmonary resuscitation (ECPR) gaining more and more importance as a rescue method in refractory OHCA ( 32 ), the question of how and when to transport a patient with OHCA will still be the subject of research in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Pensando, ainda, em reverter os mecanismos de choque o quanto antes, VA-ECMO poderia ter sido implementada durante a PCR do paciente. Uma subanálise do estudo OHCA (Out-hospital Cardiac Arrest) de Praga concluiu que o emprego de VA-ECMO após PCR refratária trouxe maior benefício de sobrevivência em 180 dias do que condução padrão baseada em suporte a vida avançado (ACLS), principalmente em paciente com ritmo chocável inicial, idade mais jovem e menor tempo de ressuscitação (ROB et al, 2022). Contudo trata-se de sub-análise de um estudo randomizado e, portanto, sujeito a variáveis de confusão (ROB et al, 2022).…”
Section: Método E Discussãounclassified